Juricultural pluralism vis-a-vis treaty law : state practice and attitudes. - Bunn-Livingstone, Sandra L. (Martinus Nijhoff Kluwer, 2002)
The way in which ""legal"" culture has been defined in the past has limited comparative processes to law itself. The author proposes a new term, ""juriculture"", defined as ""the axiological and behavioural formula which pertains to the law"". This new definition provides a comparative tool which focuses on ontological and epistemological bases of law and concomitant legal theories which are distilled from these philosophical bases, in addition to primary and secondary rules, and written laws. This book tackles the issue of how divergent individual, state, and regional cultures impact the inter.